Pengaruh Perlengkapan Kantor Terhadap Kinerja Pegawai di Kantor Desa Kertajaya Kecamatan Cigugur Kabupaten Pangandaran - Aziz, Nur; Anjani, Mutiara (JURNAL ILMIAH ILMU ADMINISTRASI, 2024)
This article discusses office equipment at the Kertajaya Village Office, focusing on the influence of office equipment on employee performance at the Kertajaya Village Office. Adequate office equipment is needed by employees. This can affect the performance of employees. The method used is a qualitative approach and case study, triangulation and questionnaires through google form as the data collection method, the number of employees/respondents is 15 people. The aim is to find out the condition of office equipment, positive and negative influences on employees at the Kertajaya Village Office. The results showed that office equipment is a tool used to help process office activities. The condition of office equipment at Kertajaya Village Office is very well maintained, as many as 73.3% of 15 employees feel that the equipment in the office is well maintained. Although there are several conditions that hinder employee performance. This is indicated by the lack of a division of office equipment, the arrangement of equipment is not neat, the procurement of equipment is not as needed, and there is no deletion. The above problems are things that can affect the work process of employees. Based on the survey results 86.7% of 15 respondents agreed that office equipment greatly affects employee performance.